Establishing Cephalometric Norms in Primary Dentition Using Comprehensive Craniofacial Growth Analysis – A Digital Cephalometric Study - Seema Deshmukh; Bhojraj Nandlal (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2023)
Objective: To establish cephalometric norms in primary dentition among males and females using novel customized Comprehensive Cephalometric Growth (CCG) Analysis. Material and Methods: The study was conducted on 67 subjects with a mean age of 5.5 yrs. Digital lateral cephalometric radiographs were obtained using Planmeca Pro One. The digital images were then transferred to Nemoceph software. Craniofacial Growth (CCG) Analysis was configured in the software with five sub-groups. This sub-grouping was done such that related components were grouped together and comprehensively; it would provide an assessment of every component of the craniofacial region that could be affected either by treatment maneuver or growth process. The same was used for the cephalometric analysis and to determine the cephalometric norms in the primary dentition. Results: Certain linear measurements were higher among males when compared to females. However, most measurements remained similar among males and females during this age group. The CCG analysis provided a comprehensive knowledge of the craniofacial parameters during the growth process. Conclusion: The cephalometric norms during primary dentition thus established using Comprehensive Craniofacial Growth analysis would provide the data for early diagnosis and treatment planning in interceptive orthodontic treatment procedures.